Drug resistance analysis of Cronobacter sakazakii from infant food in Liaoning Province - WEI Tongzhu; SUN Tingting; WANG Weijie; LI Xue (Zhongguo shipin weisheng zazhi, 2024)
ObjectiveTo investigated drug resistance of Cronobacter sakazakii in infant food after biofilms formation， and provided suggestion for drug resistance monitoring.MethodsIn this study， 58 strains of Cronobacter sakazakii， which were isolated from infant formula in Liaoning Province from 2018 to 2021， were tested to determine drug sensitivity， biofilm forming ability， and drug resistance under different biological states with 15 antibiotics.ResultsCronobacterium sakazaki detected in infant food had different degrees of resistance to cefazolin， cefotaxime， compound sulfonamide， chloramphenicol， cefoxitin， naphthalic acid， and ampicillus. In fact， 88% of the tested strains exhibited resistance to polymyxin， with multiple resistant bacteria identified. The resistance of Cronobacterium sakazaki was higher in infant milk powder source than in infant and young children. The film forming rate of the biofilm was 100%， and most medium adhesion strains accounted for 61.02% of the rate. Based on the susceptibility test results of the biofilm state corresponding to the subjects， resistance to cefazolin， cefotaxime， imipenem， tetracycline， and ampicillin increased， while that to SXT disappeared.ConclusionCronobacter sakazakii detected in infant food in Liaoning Province was resistant to cefazolin， cefotaxime， compound sulfonamide， chloramphenicol， cefoxitin， naphdidixic acid， and ampicillin. Notably， 88% of the test strains exhibited intermediate resistance to polymyxin， and multidrug-resistant bacteria were identified. Owing to the resistance to different antibiotics in infant food in Liaoning Province， monitoring the resistance to Cronobacter sakazakii in infant food sources should be strengthened.